Teknologi Ramah Lingkungan Untuk Pengendalian Hama Jeruk Siam di Desa Kuok Kecamatan Kuok Kabupaten Kampar - Hafiz Fauzana; Rusli Rustam; Fetmi Silvina; Arnis En Yulia; Muhammad Ali; Idwar Idwar; Ardian Ardian; Murniati Murniati; Gusmawartati Gusmawartati; Pajri Ananta Yudha; Dwi Ramayani; Nisa Alifia Rizki; Suci Nuratika (Riau Journal of Empowerment, 2023)
Siamese orange is a staple horticultural item in Kuok Village, Kuok District, Kampar Regency, although it is under threat from pests and illnesses. Integrated pest management emphasizes ecologically friendly pest control through the use of biological agents. The goal of this service activity is to assist Siamese citrus producers who are hampered by insect invasions and to improve farmers' skills in applying environmentally friendly control technology. Consolidation, surveys, counseling, demonstrations, and mentoring were the methods of implementation. The counseling method consists of forum presentations, questions and responses. Making PDA media, isolating, growing Metharizium sp. and Trichoderma sp., composting were all practices. The service outcomes reveal that the service activities benefit citrus producers in Kuok Village significantly. Farmers understand how to control citrus pests properly. Making PDA media , isolating, cultivating Metharizium sp. and Trichoderma spp. were examples of environmentally friendly management approaches. Farmers responded enthusiastically to the production of methankos.